THE EFFECT OF FLASH SALE AND PRICE ON IMPULSE BUYING BEHAVIOR OF MARKETPLACE USERS - Dewi Andriany; Mutia Arda (RADJA PUBLIKA, 2024)
Shopee is an e-commerce that offers online buying and selling services with various attractive features such as free shipping, cashback, flash sales at very low prices, and others. There are considerations about consumer motives and behavior when flash sales are offered which influence consumer impulsive purchasing decisions. This study aims to analyze the effect of flash sales and prices on impulse buying in Shopee marketplace users in Medan City. The research population is all Shopee Marketplace users in Medan City who have shopped at the Shopee Marketplace, the sample of this study is 100 respondents. Data collection techniques through questionnaires and data analysis using multiple linear regression analysis. The results of multiple linear regression analysis show that there is an effect of flash sales on impulse buying in marketplace users, there is no effect of price on impulse buying in marketplace users. The R-Square value of 0.818 or 81.8% shows the contribution of flash sales and prices to impulse buying in Shopee Marketplace users in Medan City and the remaining 18.2% is influenced by other variables not studied.